2018
DOI: 10.1108/ijbm-05-2017-0097
|View full text |Cite
|
Sign up to set email alerts
|

Positive moods and word-of-mouth in the banking industry

Abstract: Purpose The purpose of this paper is to examine the mediating effect of functional value and symbolic value between positive moods and word-of-mouth (WOM) referrals in the context of Taiwan’s banking industry. In addition, this study investigates the moderating effect of relational benefits on the relationship between perceived value and WOM. Design/methodology/approach The research model was tested using data collected from customers (n=362) of the top 10 domestic banks in Taiwan. Structure equation modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Moreover, while determining the online group buying intention, utilitarian shopping value appeared as the most influencing factor in the study of Lim (2017). Similarly, numerous studies also found utilitarian shopping value as a significant and one of the most influencing factors in determining customer loyalty (Hong et al, 2017;Lien, Wu, Hsu, & Wang, 2018;Verma, Jahn, & Kunz, 2012;Wang, Po Lo, Chi, & Yang, 2004). Thus, based on the above evidence from the literature, the following hypothesis has been posited.…”
Section: Corporate Imagementioning
confidence: 83%
“…Moreover, while determining the online group buying intention, utilitarian shopping value appeared as the most influencing factor in the study of Lim (2017). Similarly, numerous studies also found utilitarian shopping value as a significant and one of the most influencing factors in determining customer loyalty (Hong et al, 2017;Lien, Wu, Hsu, & Wang, 2018;Verma, Jahn, & Kunz, 2012;Wang, Po Lo, Chi, & Yang, 2004). Thus, based on the above evidence from the literature, the following hypothesis has been posited.…”
Section: Corporate Imagementioning
confidence: 83%
“…However, in this study, perceived value is measured from a functional perspective with four items. Functional value relates to the overall evaluation of value from a quality, convenience and price perspective (Lien et al , 2018). Thus, this form of value encompasses an understanding of how customers perceive value in terms of their relationship with the bank, the services delivered by the bank, the time saved when getting the service and the price paid for the service delivered (Jiang et al , 2016).…”
Section: Theoretical Framework and Hypothesis Proposedmentioning
confidence: 99%